Faktor-Faktor Penyebab Terjadinya Duplikasi Penomoran Rekam Medis Rawat Jalan Berdasarkan Aspek 5M di Puskesmas Bringin Kabupaten Semarang Tahun 2021 - Sheren Hana Abriva; Deasy Rosmala Dewi; Noor Yulia; Nanda Aula Rumana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Based on preliminary studies conducted by the author at the Bringin Community Health Center, 35 duplicate outpatient medical records were found in 2020. The purpose of this study was to identify the factors causing the duplication of outpatient medical record numbers at the Bringin Community Health Center. This study used a qualitative method with a descriptive approach. The sample in this study consisted of 4 medical record officers. The results of the study in February-March 2021 showed that there were two duplicate medical record numbers. The causes of duplicate medical record numbering were based on the 5M aspects (Man, Material, Method, Machine, Money). The man factor was related to the limited number of staff. The material factor was related to patients who did not bring their medical treatment identity card when visiting. The method factor indicates the lack of specific standard operating procedures regarding medical record numbering. The machine factor indicates that the system is still manual. The money factor indicates a lack of funds needed to add medical record staff. The recommendation to the Bringin Community Health Center is to create standard operating procedures for Medical Record Numbering and provide training for staff who are not medical record graduates.